1999
DOI: 10.1074/jbc.274.21.14909
|View full text |Cite
|
Sign up to set email alerts
|

The RACK1 Signaling Scaffold Protein Selectively Interacts with the cAMP-specific Phosphodiesterase PDE4D5 Isoform

Abstract: The WD-repeat protein receptor for activated C-kinase (RACK1) was identified by its interaction with the cyclic AMP-specific phosphodiesterase (PDE4) isoform PDE4D5 in a yeast two-hybrid screen. The interaction was confirmed by co-immunoprecipitation of native RACK1 and PDE4D5 from COS7, HEK293, 3T3-F442A, and SK-N-SH cell lines. The interaction was unaffected by stimulation of the cells with the phorbol ester phorbol 2-myristate 3-acetate. PDE4D5 did not interact with two other WD-repeat proteins, ␤'-coatomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
284
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(290 citation statements)
references
References 46 publications
6
284
0
Order By: Relevance
“…The interaction was con®rmed by co-immunoprecipitation of PDE4D5 with native RACK1 in Cos7 cells. No binding is observed with other WD40 proteins including eRACK (Yarwood et al, 1999). Although, interaction of PDE4D5 with RACK1 is not a ected by PMAstimulation of the cells, binding of PDE4D5 to RACK1 increases the sensitivity of the enzyme to its inhibitor, rolipran (Yarwood et al, 1999).…”
Section: Phosphodiesterase 4d5mentioning
confidence: 90%
See 1 more Smart Citation
“…The interaction was con®rmed by co-immunoprecipitation of PDE4D5 with native RACK1 in Cos7 cells. No binding is observed with other WD40 proteins including eRACK (Yarwood et al, 1999). Although, interaction of PDE4D5 with RACK1 is not a ected by PMAstimulation of the cells, binding of PDE4D5 to RACK1 increases the sensitivity of the enzyme to its inhibitor, rolipran (Yarwood et al, 1999).…”
Section: Phosphodiesterase 4d5mentioning
confidence: 90%
“…A yeast two-hybrid screen also demonstrated that RACK1 binds the cAMP phosphodiesterase isoform 4D5 (PDE4D5) (Yarwood et al, 1999). The interaction was con®rmed by co-immunoprecipitation of PDE4D5 with native RACK1 in Cos7 cells.…”
Section: Phosphodiesterase 4d5mentioning
confidence: 97%
“…The scaffolding protein RACK1, which was originally identified as an anchoring protein of protein kinase C ␤II (2), belongs to the WD40 family of proteins characterized by seven WD40 repeats forming a seven-blade ␤-propeller structure (3,4). This particular structure allows RACK1 to interact with various enzymes including Fyn kinase (5), focal adhesion kinase (6), receptor protein tyrosine phosphatase (7), the cyclic AMP-specific phosphodiesterase (PDE4) isoform PDE4D5 (8), as well as the intracellular tails of receptors such as the insulin-like growth factor 1 receptor (IGF-1R) (9,10), the inositol 1,4,5-triphosphate receptor (11), and ion channels such as the NR2B subunit of the N-methyl D-aspartate receptors (5). These interactions, and others, put RACK1 at a focal point for spatial and temporal regulation of various signaling cascades.…”
mentioning
confidence: 99%
“…The physical interaction between RACK1 and integrin b subunit or Src is dependent on the stimulation of cells with phorbol ester PMA (Liliental and Chang, 1998;Chang et al, 2001), suggesting that PKC activation is required for the above interaction. On the other hand, the interaction of RACK1 with the common b-chain of the cytokine receptors, cAMPspecific phosphodiesterase isoform PDE4D5 or BZLF1 is constitutive and unaffected in the presence of PMA (Geijsen et al, 1999;Yarwood et al, 1999;Baumann et al, 2000). Thus, RACK1 appears to be associated with cellular proteins in a manner dependent or independent on the PKC activation.…”
Section: Discussionmentioning
confidence: 86%